The Impact of Product Presentation Quality on Consumer Enjoyment and Impulsive Buying Decision When Doing e-Leisure Shopping Activity. - Kristanto, Damar; Suharto, Bambang; Aly, M. Nilzam; Yuliawan, Rahmat; Salam, Moh. Darus; Nata, Jiwangga Hadi (International Journal of Psychosocial Rehabilitation, 2020)
Currently, leisure activities can not only be done physically but can also be done through online media. Leisure activities conducted online can be referred to as e-leisure activities. One form of e-leisure is online shopping. This e-leisure activity must be supported by strong stimuli. In previous studies, the form of stimuli discussed was often the problem of the atmosphere of online stores, but when viewed from the viewpoint of window shopping behavior, the best stimuli for increasing consumer enjoyment should be the quality of product presentations in online stores in the form of visual stimuli and textual information. Enjoyment in online shopping activities can also encourage consumers to be impulsive in buying, so the purpose of this study is to link between perceived quality of product presentation, enjoyment and impulsive behavior in buying when doing e-leisure activities in online stores. This study drew a sample of 500 respondents. The hypothesis in the research model was analyzed using partial least square. The results showed that the quality of product presentations in online stores had an impact on the enjoyment and impulsive buying behavior. The implication of this research is to understand that the quality of online product presentations can affect the quality of consumer enjoyment in their e-leisure activities so that retailers must pay more attention to these factors.